MODEL E-READINESS PENGGUNA SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) PADA KANTOR URUSAN AGAMA KECAMATAN CIGUGUR KABUPATEN PANGANDARAN - Santi Nurmalasari; Khaerul Umam; Herabudin Herabudin (Sekolah Tinggi Pariwisata Mataram, 2022)
The main problem of this research is that to apply e-government, indeed, a readiness of user is needed. The users here refer to the staff of the Religious Affairs Office (KUA) of Cigugur District and the societies holding weddings in 2020. One of the inhibiting factors in implementing this SIMKAH application is the readiness of users and information about SIMKAH application is still not widely disseminated. Thus, the information cannot be conveyed effectively to the public. The aim of this research is to analyze E-readiness Pengguna Sistem Informasi Manajemen Nikah (SIMKAH) at Religious Affairs Office (KUA) in Cigugur District, Pangandaran. The research employs descriptive methods and a qualitative approach. The data is being collected through observation and interviews. Analyzing the data involves reducing the amount of data, presenting the data, and drawing conclusions. Overall, it can be concluded from the results and discussions above that the Office of Religious Affairs (KUA) in Cigugur District of Pangandaran Regency is quite ready to use the Marriage Management Information System (SIMKAH). It is based on several factors, including Network Access, Community Access, Economic Access, and Policy Access to support users of the marriage management information system (SIMKAH) in Cigugur District, Pangandaran Regency.